Attitudes of Arabic Language Teachers Towards the Use of Differentiated Teaching Strategies When Teaching the Grammatical Function - Daghriri, Abdullah Yahya; Alkahtani, Adel Abdullah (Journal of Educational and Psychological Sciences, 2021)
The aim of this research is to uncover the attitudes of Arabic language teachers towards using differentiated teaching strategies while teaching the grammatical function of middle school students, and the effect of each of their academic qualifications, teaching experience and training courses on their attitudes towards these strategies. The researchers used the descriptive and analytical method. The sample of the study consisted of (103) middle school Arabic language teachers in Jeddah, who were randomly selected. The study used a questionnaire tool, where its paragraphs were formulated according to the gradation of the five-dimensional Likert scale. The results of the research found that the overall average of grades of estimating attitudes of Arabic language teachers towards the use of differentiated teaching strategies Reached (3.71) with a response score (Agree); Which indicates the presence of the positive trend they have, as well as the same response in each axis of the tool, and the results also showed that there are no statistically significant differences at the level (α≤0.05 (between the average responses of the sample members in the trends as a whole due to the two variables (qualification type The teaching experience), and in the variable (training courses), we found statistically significant differences at the level of (α≤0.05 (between the average responses of the sample members in the attitudes as a whole in favor of the training courses. The study recommended holding more training courses related to differentiated teaching and its strategies, how to employ them with Arabic language lessons, also recommended the need to deepen the skill of the grammatical function in students’ minds by employing differentiated teaching strategies that support this.